Determination of nitrate in the edible part of vegetables from markets around Chiang Mai city, Northern Thailand by using high performance liquid chromatography - Surat Hongsibsong (2018)
© 2014 Knowledgia Review, Malaysia. Vegetables play a popular food among consumer who needs the healthy food in Chiang Mai, Thailand. The quality and safety food was the main thing that is guarantee for vegetable products which sold in the markets. Nitrate is the one chemical that has reported contamination in vegetables. The level of nitrate content in vegetable products from hydroponic and conventional system will be interested. So, this study aimed to investigate the amounts of nitrate in vegetable products from hydroponic and conventional vegetable products which sold in markets around Chiang Mai city. The common vegetables were 3 cross-sectional sampling from retailer market in 2013 around Chiang Mai city, northern Thailand. All samples were prepared and measured the nitrate content using HPLC method. The mean nitrate concentrations in vegetable products from hydroponics and conventional system were compared. There was found that nitrate concentrations in lettuce hydroponics products were significantly higher than conventional in every season. Kale, flowering Chinese cabbage and Pak Choi contained very high nitrate contents with mean of nitrate concentrations higher than 3,000 mg kg -1 (fresh weight). In conclusion, the level of nitrate in both hydroponic and conventional lettuces samples from Chiang Mai city, northern Thailand in 2013 were lower than EU-MRL except conventional kale, flowering Chinese cabbage and Pak Choi samples have the high concentration but no MRL established yet. In comparison of type of markets show no significant difference of nitrate content in vegetable products so consumer can be bought less nitrate contamination in vegetable from all type of markets.